THE INFLUENCE OF AUDIT TENURE, INDEPENDENT COMMISSIONER, AUDIT COMMITTEE, AND AUDIT QUALITY ON INTEGRITY OF FINANCIAL STATEMENTS. (Empirical Study on Property and Real Estate Sub Sectors Listed on the Indonesia Stock Exchange) - Gine Das Prena (Fakultas Ekonomi Universitas Negeri Jakarta, 2020)
The purpose of this study is to find out the variables that can affect the integrity of the report by examining audit tenure, independent commissioners, audit committees, and audit quality. This research was conducted on the property and real estate sub-sectors listed on the Indonesia Stock Exchange for the period 2015-2018. This study uses secondary data, namely annual financial reports issued by the company. By using the purposive sampling method then using the pooled method obtained 156 samples. The analysis technique used is multiple linear regression, classical assumption test and significance test. Partially 1) Audit tenure has no significant effect on the integrity of financial statements. 2) Audit committee has no significant effect on the integrity of financial statements, 3) audit committees have no significant effect on the integrity of financial statements, 4) audit quality has a significant effect on the integrity of financial statements, while simultaneously audit tenure, independent commissioners, audit committees and influential audit quality significant to the integrity of financial statements.Keywords: Tenure Audit, Independent Commissioner, Audit Committee, and Audit Quality, Financial Report Integrity